Effects of long-term air pollution exposure on ankle-brachial index and cardio-ankle vascular index: A longitudinal cohort study using data from the Electricity Generating Authority of Thailand study - Kanawat Paoin (2022)
Background: Ankle-brachial index (ABI) and cardio-ankle vascular index (CAVI) are surrogate measures of atherosclerosis based on the functional performance of vessels, and are highly related to cardiovascular events. However, only a few longitudinal studies have been conducted on their associations with long-term air pollution exposure. Objective: This study aimed to examine whether long-term air pollution exposure is associated with ABI and CAVI in workers of the Electricity Generating Authority of Thailand (EGAT) in the Bangkok Metropolitan Region (BMR). Methods: This longitudinal study included 1261 participants (age range, 57–76 years as of 2007) of the EGAT study (2007–2017). ABI and CAVI were measured in 2007, 2012, and 2017. Annual mean concentrations of particulate matter ≤10 μm in diameter (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), ozone (O3), and carbon monoxide (CO) were estimated by ordinary kriging using data from 22 background and 7 traffic monitoring stations in BMR between 2002 and 2017. Linear mixed-effects models were used to assess associations between air pollution (expressed as 1-year, 3-year, and 5-year average concentration) and ABI and CAVI (expressed as percent changes per interquartile range (IQR) increase in PM10, O3, NO2, SO2, and CO). We also applied the mixed-effect ordinal logistic models to calculate odds ratios (ORs) of having high or moderate CAVI per an IQR increase in air pollution. Results: After controlling for potential confounders, 1-year average CO was negatively associated with ABI, but not significantly (−0.48%, 95% CI: −1.03, 0.07). Three-year average NO2 was positively associated with CAVI (6.67%, 95% CI: 0.21, 13.1). In contrast, 1-year average PM10 was inversely associated with CAVI although the association was not significant. Although not significantly, 1-year average NO2 and CO were positively associated with prevalence of high or moderate CAVI. Conclusions: Although not statistically significant, long-term NO2 and CO exposure was associated with ABI and CAVI in the participants of the EGAT study.